Synthesis and characterization of phthalonitrile resins from ortho‐linked aromatic and heterocyclic monomers. Issue 3 (9th May 2013) - Badshah, Amir; Kessler, Michael R; Heng, Zhou; Hasan, Aurangzeb
<x xml:space="preserve">Abstract</x> Novel polymers were synthesized from ortho‐linked monomers containing aromatic and heterocyclic rings, maintaining excellent structural integrity. The oxadiazole‐containing polymer exhibited neither glass transition temperature nor any change in storage modulus up to 500 °C. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>